Pengembangan Sistem Informasi Izin Kerja Dan Praktik Tenaga Kesehatan (SINKES) Dinas Kesehatan Kota XYZ - Rosalia Indah; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinas Kesehatan Kota XYZ is the implementing element of health sector in XYZ City Government led by a Head of Service responsibles to the Regional Secretary. One of the duties of Dinas Kesehatan (Dinkes) is to provide services for Health Workers who work in its administrative region. In the application for a work or practice permit process, Health Workers may go to the Dinkes office more than one time just to fullfill the requirement files, because the application will not be handled if it is not appropriate. Meanwhile, from the Dinkes side, the handling of the application will be impeded if the authorized officers are not in place because the printed file submitted by the Health Workers must be checked directly. Based on these conditions, an information system developed for the application of work and practice permits that can be used by Health Workers and Dinas Kesehatan Kota XYZ to apply and handle the submitted applications. This information system also provides the Health Workers to know the stages of handling that is being done by Dinkes officer, so that information related to work permit can be more transparent. In this study, V-Model was chosen as the software development method used during development. Furthermore, the results of the implementation of the functions are tested using responsiveness testing, compatibility testing and user acceptance testing.